OVERVIEW AND NECESSITY OF RISK MANAGEMENT IN TOURISM - Oliver FILIPOSKI, Milena TALESKA, Kristijan DZAMBAZOVSKI, Chedomir DIMOVSKI (TURISTIKA, 2021)
The need for risk management in tourism is as great as ever. The purpose of this study is to present the ways of managing risks in tourism and the need to establish a system for risk management at the state level and in enterprises within the tourism industry. Through the analysis of the already known literature in the field of risk management which is slightly adapted to the tourist’s needs, analysis of the risk management standards, policies and procedures that were introduced in the world and the Republic of North Macedonia due to the COVID‐19 pandemic, we will perceive the need for a systemic approach to tourism risk management at both, macro and micro levels. The results show the framework of the processes for tourism risk management which is adaptable to the needs of the tourism industry.
Keywords: tourism, risk management, risk management process